Policy capacities for driving sustainable development: A comparison of two regional governments in Peru - Alcalde, Gonzalo (2025)
Twenty years after the creation of Peruvian regional governments (GOREs), this research identifies factors that can explain the attainment of different levels of policy capacities for development, starting from similar regulatory and organizational frameworks. The study examines the markedly different capacities achieved by two Amazonian regional governments (GOREs) by 2018: San Martín and Madre de Dios. The findings suggest that structural and institutional factors that predate the creation of these governments are fundamental to understanding their distinct trajectories, to an equal or greater extent than decisions by regional actors or rules applied since the creation of GOREs.